Lymphoid Interstitial Pneumonia in Common Variable Immune Deficiency – Case Report With Disease Monitoring in Various Therapeutic Options: Pleiotropic Effects of Rituximab Regimens - Zdziarski, Przemyslaw; Gamian, Andrzej (Frontiers in Pharmacology, 2019)
Lymphoid interstitial pneumonia (LIP) is a rare lymphoproliferative disease. LIP in common variable immune deficiency (CVID) was observed in a patient during immunomodulatory therapy after progression of the disease (i.e. glucocorticoids, immunoglobulin dose escalation and finally rituximab). Due to humoral immunodeficiency and serious serum sickness rituximab was used initially at a low dose (150 mg/m2 weekly). It resulted in temporary remission with the decrease of serum paraproteinemia, β2-microglobuline (β2M) and SUV decrease as well as increase of FVC. Owing to the relapse after six-month remission in the second cycle a standard dose of rituximab was used (375mg/m2). Therapeutic regimen with 375 mg/m2 of Rtx in optimal schedule (i.e. every 3 weeks) resulted in no longer remission but higher incidence of opportunistic infections. Finally, after another cycle of immunotherapy FVC, paraproteinemia and β2M level normalization were observed as well as the decrease of severe splenomegaly. In laboratory and immunological progress the increase of NK and NKT cells was observed after the initial dose but the standard one caused NK cell increase only. Unfortunately, the decrease of CD19+Bcells was comparable between both doses, as was the decline of FoxP3+ regulatory T cell. On the contrary, after the low dose absolute T cell (both CD4 and CD8) number decreased but after the standard one - it normalized. Rtx (especially in low dose) brought further increase of persistent T cell activation(CD38+ T cells made up 79%). Innate immune response and the decrease of Treg are a compensatory pathways for the decrease of B and T cells. Immunodeficiency requires a different investigative approach to a immunotherapy.